PEMANFAATAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN PAI DI SD NEGERI CANDIREJO - Bekti Taufiq Taufiq Ari Nugroho; Mustaidah . (Jurnal Progress)
Abstrac Utilization of Information Technology for Learning Islamic Education (PAI) in SD Negeri Candirejo can be grouped into three functions, namely: a) Independent / classical learning media; 2) Information Technology that is used for learning aids; 3) Information Technology related as a source of learning (learning resurces). Development of learning programs at SD Negeri Candirejo, namely: a) Behavioral technology program stage; b) Stage instructional technology; c) Stage performance technology. SD Negeri Candirejo, needs to use and maximize learning media that can support the development of Islamic religious education itself. PAI teachers at Candirejo Public Elementary School will play a role in managing the entire learning process by creating learning conditions in such a way that each child can learn effectively and efficiently. Starting from choosing materials, theories, methods, techniques, strategies and learning media. As an assessment of student learning outcomes (evaluator of student learning), teachers are required to play a role in continuously following the learning outcomes achieved by students from time to time. As a director of learning (teacher of learning), the teacher has a role to always generate, maintain, and increase the motivation of students to learn and as a guide in learning. Keywoard: Utilization of Information Technology, Learning PAI Abstrak Pemanfaatan Teknologi Informasi untuk Pembelajaran Pendidikan Agama Islam (PAI) di SD Negeri Candirejo dapat dikelompokkan ke dalam tiga fungsi, yaitu: a) Media Pembelajaran mandiri/klasikal; 2) Teknologi Informasi yang dimanfaatkan untuk alat bantu pembelajaran; 3) Teknologi Informasi yang terkait sebagai sumber belajar ( learning resurces). Pengembangan program belajar di SD Negeri Candirejo yaitu: a) Tahap program behavioral technology; b) Tahap instructional technology; c) Tahap performance technology. PROGRESS – Volume 7, No. 1, Juni 2019 1 Jurnal Pendidikan Agama Islam Universitas Wahid Hasyim SD Negeri Candirejo, perlu menggunakan dan memaksimalkan media pembelajaran yang dapat menunjang terhadap pengembangan pendidikan agama Islam itu sendiri. Guru PAI di SD Negeri Candirejo akan berperan mengelola seluruh proses pemeblajaran dengan menciptakan kondisi-kondisi belajar sedemikian rupa sehingga setuiap anak dapat belajar secara efektif dan efisien. Mulai dari memilih materi, teori, metode, teknik, strategi maupun media pembelajaran. Sebagai penilai hasil belajar siswa (evaluator of student learning), guru dituntut untuk berperan secara terus-menerus mengikuti hasil-hasil belajar yang dicapai oleh siswa dari waktu ke waktu. Sebagai pengarah belajar ( director of learning), guru berperan untuk senantiasa menimbulkan, memelihara, dan meningkatna motivasi siswa untuk belajar dan sebagai pembimbing dalam belajar. Kata Kunci: Pemanfaatan Teknologi Informasi, Pembelajaran PAI